A clinician's guide to making a diagnosis of atopic dermatitis in dogs. Issue 4 (1st May 2020) - Barnard, Natalie
Abstract : Background: The pruritic dog is a common, non‐specific clinical presentation seen in general practice that can have many different causes. A diagnosis of atopic dermatitis can only be made by excluding all other causes of pruritus. The diagnostic pathway is a process clients often find frustrating because it is lengthy and requires a lot of commitment on their part with regards to time and money. Atopic dermatitis is a disease which can be controlled but not cured, so it is vital to have the correct diagnosis before starting the patient on a lifelong treatment regime. Aim of the article: This article, the first in a three‐part series on atopic dermatitis, discusses the diagnostic steps that need to be taken to reach a diagnosis of atopic dermatitis. Parts 2 and 3, to be published in future issues of In Practice, will cover management of atopic dermatitis and how to use in‐house dermatological tests.